An Orders‐of‐Magnitude Increase in the Rate of the Solid‐Catalyzed CO Oxidation by In Situ Ball Milling1. Issue 48 (23rd September 2013) - Immohr, Sarah; Felderhoff, Michael; Weidenthaler, Claudia; Schüth, Ferdi
<x xml:space="preserve">Abstract</x> Shaken, not stirred: CO oxidation was carried out continuously in a shaker ball mill. During milling, the reaction rate increases dramatically, but drops rapidly to zero when the mill is stopped. Compared to a conventional experiment in a plug‐flow reactor, the rate of a ball‐mill reaction catalyzed by Cr2O3 is three orders of magnitude higher at room temperature and one order of magnitude higher at 100°C.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>